Continuous mode voltage fed inverter - MIESKOSKI JAMES D; NERONE LOUIS R (2005)
In accordance with one aspect of the present application, a continuous mode voltage fed inverter includes a resistor starting network configured to start a charging of the inverter. A resonant feedback circuit is configured to generate an oscillating signal following the starting of operation of the circuit by the resistor starting network. A complementary switching network has a pair of complementary common source connected switches configured to receive the oscillation signal generated by the resonant feedback circuit, wherein the oscillation signal determines a switching rate of the complementary pair of switches. A clamping circuit is configured to maintain an inverter current in an inductive mode, wherein the inductive current lags voltage across the pair of complementary common source connected switches. A fold-back circuit is connected, in one embodiment, to the complementary switching network to provide a two-level clamping action. A first-level clamps the output voltage sufficient to permit a starting of the lamp. A second level of the two-level clamping arrangement of the fold-back circuit clamps the output voltage to protect the inverter from overheating when a lamp is removed from the circuit.